2013
DOI: 10.21608/absb.2013.6463
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Biological Activity of Thiourea Containing Polymers

Abstract: N-acryloyl-N-phenylthiourea (APTU) is synthesized by reacting acryloyl chloride with phenylthiourea in the presence of triethylamine (TEA) as a base and characterized by FT-IR, 1 H-NMR and mass spectra. The acrylic polymers from different feed ratios of ethylacrylate (EA), methylmethacrylate (MMA), styrene (St) and APTU have been prepared by emulsion polymerization in water containing sodium lauryl sulfate as a surfactant and ammonium persulfate as a water-soluble radical initiator. The polymers are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Thermal degradation kinetic parameters are determined for polymer samples From TGA curves using Broido’s, Coats–Redfern and Horowitz-Mitzger methods which provide overall kinetic data. The present study revealed that the values of energy of activation for all the equations applied follow the order: Step II > Step I [ 19 ]. A series of functionalized phenolformaldehyde polymer resins have been synthesized by the reactionof 2,4-dihydroxyacetophenone-formaldehyde resin with theamines, such as ethanolamine, aminophenol, ethylenediamine, and propylenediamine in dichloromethane.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal degradation kinetic parameters are determined for polymer samples From TGA curves using Broido’s, Coats–Redfern and Horowitz-Mitzger methods which provide overall kinetic data. The present study revealed that the values of energy of activation for all the equations applied follow the order: Step II > Step I [ 19 ]. A series of functionalized phenolformaldehyde polymer resins have been synthesized by the reactionof 2,4-dihydroxyacetophenone-formaldehyde resin with theamines, such as ethanolamine, aminophenol, ethylenediamine, and propylenediamine in dichloromethane.…”
Section: Discussionmentioning
confidence: 99%